2020
DOI: 10.1093/geronb/gbaa152
|View full text |Cite
|
Sign up to set email alerts
|

What Determines Cognitive Functioning in the Oldest-Old? The EMIF-AD 90+ Study

Abstract: Objectives Determinants of cognitive functioning in individuals aged 90 years and older, the oldest-old, remain poorly understood. We aimed to establish the association of risk factors, white matter hyperintensities (WMH), hippocampal atrophy and amyloid aggregation with cognition in the oldest-old. Methods We included 84 individuals without cognitive impairment and 38 individuals with cognitive impairment from the EMIF-AD 90… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 66 publications
1
27
0
Order By: Relevance
“…Slower rates of memory decline have also been associated with larger baseline whole brain volume across the older adult lifespan (Carmichael et al, 2012). Cross-sectional studies similarly report that oldest-old adults with larger hippocampus volumes have better episodic memory performance (Eguchi et al, 2019) and faster processing speeds (Legdeur et al, 2020;Pelkmans et al, 2021), comparable to what has been reported in younger-old adults (Carr et al, 2017;Gorbach et al, 2017;O'Shea et al, 2016).…”
Section: Neurocognitive Aging In the Oldest-oldmentioning
confidence: 65%
“…Slower rates of memory decline have also been associated with larger baseline whole brain volume across the older adult lifespan (Carmichael et al, 2012). Cross-sectional studies similarly report that oldest-old adults with larger hippocampus volumes have better episodic memory performance (Eguchi et al, 2019) and faster processing speeds (Legdeur et al, 2020;Pelkmans et al, 2021), comparable to what has been reported in younger-old adults (Carr et al, 2017;Gorbach et al, 2017;O'Shea et al, 2016).…”
Section: Neurocognitive Aging In the Oldest-oldmentioning
confidence: 65%
“…Although the importance of some risk factors for dementia appears to decline with increasing age, other risk factors have drawn attention in the oldest-old. Lower physical strength and performance, less participation in cognitive stimulating activities, and lower kidney function have been associated with cognitive impairment in the oldest-old [ 17 ▪ , 18 ▪ , 19 ]. Although it is difficult to disentangle cause and effect in these relationships, preserving physical health seems to be of utmost importance to preserve cognitive health in the oldest-old [ 20 ].…”
Section: Text Of Reviewmentioning
confidence: 99%
“…A recent review of neuroimaging findings in the oldest-old (Woodworth D, Scambray K, Corrada MM, Kawas CH, Sajjadi AS, manuscript under review) noted a lack of imaging studies in this age group. In general, studies found greater global, medial temporal, or hippocampal atrophy to be related to dementia risk [ 35 ], cognitive performance [ 18 ▪ , 36 ▪▪ , 37 ▪▪ ] and faster rates of cognitive decline [ 37 ▪▪ , 38 ▪ ]. High burden of white matter lesions was also a common finding and was associated with worse baseline scores and faster decline in measures of global cognition [ 18 ▪ , 37 ▪▪ ].…”
Section: Text Of Reviewmentioning
confidence: 99%
See 2 more Smart Citations